Physical therapy gait assessment based on smart sensing and cloud services - Batoca, P.; Postolache, O.; Correia, A. (2022 International Symposium on Sensing and Instrumentation in 5G and IoT Era (ISSI), 2022)
This article describes the development of a solution to tackle the lack of data that physiotherapists have during physical rehabilitation with walking aids. The developed system is based on an ESP32 microcontroller connected to an RFID reader, load cells, and an IMU mounted in a crutch. The data from the measurement channels associated with the smart crutch are acquired and sent to a cloud data storage using WiFi and MQTT protocol. A server application is available for physiotherapists and patients to view and analyze the data from each session. Experimental results are included in the paper associated with system validation with volunteers.